Ефект ацетил-L-карнiтину на мiтохондрiальну функцiю та вивiльнення серотонiну при цукровому дiабетi - Кучмеровська, Т.М.; Шиманський, I.О.; Донченко, Г.В.; Янiцька, Л.В.; Копелевич, В.М.; Клименко, А.П. (Видавничий дім "Академперіодика" НАН України, 2008)
A close relation between the impaired energy metabolism and the serotonin release from isolated synaptic terminals is established. These data suggest a substantial role of mitochondria in the derangement of the synaptic function associated with diabetes. Positive neuromodulatory role of acetyl-L-carnitine on the serotoninergic system is found. It is most likely to be mediated by it’s normalizing effect on the energy metabolism.